Regional Economic Outlook, October 2018, Western Hemisphere Department : An Uneven Recovery. - International Monetary Fund. Western Hemisphere Dept. (Washington, D.C. : International Monetary Fund, 2018)
Amid escalating trade tensions, tighter financial conditions, and volatile commodity markets, economic recovery in Latin America and the Caribbean has both moderated and become more uneven.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet